Mejoramiento genético y actividades relacionadas. Mejoramiento de características individuales. Resistencia a plagas invertebradas - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The search for new sources of resistance to Empoasca kraemeri, Acanthoscelides obtectus, Zabrotes subfasciatus, and Apion godmani among bean germplasm materials continued in 1986. Special emphasis was placed on the study of mechanisms of resistance to E. kraemeri, A. obtectus, and Z. subfasciatus and in the reorganization of a network to evaluate resistance to A. godmani in Central America. Studies on the biology, ecology, mass rearing, and possible var. preferences of Bemisia tabaci and Trialeurodes vaporariorum were also initiated. Results are included in table form. (CIAT)